2021
DOI: 10.21203/rs.3.rs-279349/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Use of Ondansetron for the Treatment of Nausea in Dogs With Vestibular Syndrome

Abstract: Background: Vestibular syndrome is often accompanied by nausea. Drugs currently approved for its treatment have been developed to stop vomiting but not nausea. The efficacy of 5‑HT3 receptor antagonists to reduce nausea has been described for chemotherapy, but not for nausea secondary to vestibular disorders.Methods: Sixteen dogs with vestibular syndrome-associated nausea were included in the open-label, multicentric study. The intensity of nausea-like behaviour was analysed before ondansetron administration (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 48 publications
2
6
0
Order By: Relevance
“…These results have been observed in other experimental studies, such as in dogs with renal disease or when used against preoperative nausea 19,22,35 . After promising results when using ondansetron against vestibular nausea, 28 our current study emphasizes further the potential for the use of ondansetron to treat nausea resulting from vestibular syndrome in dogs.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…These results have been observed in other experimental studies, such as in dogs with renal disease or when used against preoperative nausea 19,22,35 . After promising results when using ondansetron against vestibular nausea, 28 our current study emphasizes further the potential for the use of ondansetron to treat nausea resulting from vestibular syndrome in dogs.…”
Section: Discussionsupporting
confidence: 81%
“…Our objective was to further evaluate the efficacy of ondansetron in a randomized, placebo‐controlled, double‐blinded, cross‐over study, after promising results in a previous preliminary study 28 . Our study confirmed the results of the first open‐labeled study.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations